A Randomized Controlled Trial of Naloxone for Optimization of Hypoxemia in Lung Donors After Brain Death. Issue 7 (July 2019) - Dhar, Rajat; Stahlschmidt, Emily; Paramesh, Anil; Marklin, Gary
Abstract : Background: Persistent hypoxemia is the principal reason lungs from otherwise eligible brain dead (BD) organ donors are not transplanted. Experimental models and retrospective studies have suggested that naloxone attenuates neurogenic pulmonary edema and reverses hypoxemia after brain death. We undertook a multisite, randomized, placebo-controlled trial to evaluate whether naloxone is able to improve oxygenation in BD donors with hypoxemia. Methods: BD organ donors at 4 organ procurement organizations were randomized in a blinded manner to naloxone 8 mg or saline placebo if lung were being considered for allocation but exhibited hypoxemia (partial pressure of oxygen in arterial blood to fraction of inspired oxygen ratio [PFR] below 300 mm Hg). The primary outcome was change in PFR from baseline to final arterial blood gas. Secondary outcomes included early improvement in PFR and proportion of lungs transplanted. Results: A total of 199 lung-eligible BD donors were randomized to naloxone (n = 98) or placebo (n = 101). Groups were comparable at baseline. Both groups exhibited similar improvements in oxygenation (median improvement in PFR of 81 with naloxone versus 80 with saline, P = 0.68), with 37 (39%) versus 38 (40%) exhibiting reversal of hypoxemia. There was no difference in the rate of lungs transplanted (19% in both groups, P = 0.97) although it was significantly higher in those with reversal of hypoxemia (32/69 versus 2/111, P < 0.001). Conclusions: Naloxone does not improve oxygenation more than placebo in hypoxemic organ donors. However, reversal of hypoxemia was a powerful predictor of lung utilization regardless of drug therapy. Further organ procurement organization–led research is needed to assess optimal interventions to improve oxygenation in BD donors with hypoxemia.